Zombie International Currency: The Pound Sterling 1945-1971 - Avaro, Maylis (My University, 2024)
This paper examines the international role of sterling during the Bretton Woods era and argues that it was not a competitor to the U.S. dollar. I construct a novel dataset to measure the reserve role of sterling in Europe and sterling area countries. The postwar reserve role of sterling was limited to the sterling area and was artificial as this area was built as a captive market. I document how British authorities imposed exchange controls, commercial threats, and economic sanctions on sterling area countries to compel them to keep their foreign exchange reserves in sterling.
PUBLISHED
Keywords: International Development; International Integration; Making Ireland; ECONOMIC HISTORY; EU Politics; Macroeconomics, open economy, international; Political Economy; History